2009
DOI: 10.1080/09513590902730762
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of the ER22/23EK polymorphism against an excessive weight gain during pregnancy

Abstract: It has been shown that women who gained an excessive weight during pregnancy had an increase in long-term BMI compared with those without an excessive weight gain. Several studies have demonstrated that some polymorphisms of the glucocorticoid receptor (GR) gene may influence body composition and metabolic parameters. In the present study, we wanted to explore whether any association could exist between the BclI, N363S and ER22/23EK polymorphisms of the GR gene and the weight gain during pregnancy. We found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
(28 reference statements)
0
4
0
1
Order By: Relevance
“…For example, the ER22/23EK (rs6189 and rs6190) polymorphism, which occurs in about 3% of the population, is associated with a more favorable metabolic profile, including a lower risk of both type 2 diabetes and cardiovascular disease [50]. This effect is conferred via reduced glucocorticoid sensitivity, which is mediated by a change from GAG AGG to GAA AAG in exon 2 at position 23 within the NTD [72,73].…”
Section: Gr Polymorphismsmentioning
confidence: 99%
“…For example, the ER22/23EK (rs6189 and rs6190) polymorphism, which occurs in about 3% of the population, is associated with a more favorable metabolic profile, including a lower risk of both type 2 diabetes and cardiovascular disease [50]. This effect is conferred via reduced glucocorticoid sensitivity, which is mediated by a change from GAG AGG to GAA AAG in exon 2 at position 23 within the NTD [72,73].…”
Section: Gr Polymorphismsmentioning
confidence: 99%
“…The ER22/23EK polymorphism is associated with a healthy metabolic and inflammatory profile, characterized by lower total cholesterol and low-density lipoprotein cholesterol levels as well as lower fasting insulin concentrations, a better insulin sensitivity and lower C-reactive protein levels [31,34]. This GR variant is also associated with a beneficial body composition, shown by young male ER22/23EK carriers (taller, stronger and more muscle mass than noncarriers) and female ER22/23EK carriers (tendencies for smaller waist and hip circumferences, lower body weight [35], and protective effect on weight gain during pregnancy [32,36]). These associations of the ER22/23EK polymorphism are in line with a mild GR resistance.…”
Section: Genetics Of Hpa Axis: Consequences For Physical and Mental Hmentioning
confidence: 99%
“…Conflicting results have been also reported for the ER22/23EK polymorphism in general population. Some studies demonstrated higher cortisol levels after dexamethasone suppression associated to increased insulin sensitivity, better metabolic profile and reduced weight, although with a striking gender difference in the SNP effect [ 3 , 8 , 33 , 34 ]. Other studies did not confirm these data [ 26 , 35 ].…”
Section: Discussionmentioning
confidence: 99%